Rapid determination of desorption efficiency, and analysis of solvent mixtures for occupational exposure studies - Lepera, José Salvador [UNESP]; Colacioppo, S. (Vieweg, 2002)
An analytical procedure has been developed for simultaneous determination of solvent mixture vapors to enable evaluation of occupational exposure. To determine the desorption efficiency the volatile components of the solvent mixtures were generated from a glass tube filled with glass wool. This device is easy to prepare and use. These vapors were then collected in activated charcoal tubes and analyzed by capillary gas chromatography. The method was tested with a mixture of 22 solvents, including aliphatic and aromatic hydrocarbons, alcohols, ethers, esters, and ketones, oil at low concentrations. All the components were defected. When a 99: 1 mixture of carbon disulfide-dimethylformamide was used for desorption the efficiency was > 75% for most of the solvents.
Keywords: gas chromatography; activated charcoal adsorption; solvent mixtures; desorption efficiency; occupational hygiene studies